ECONOMICS OF MILK PRODUCTION IN PLAIN AND HILL REGIONS OF UTTARAKHAND STATE+ - Vishnoi, Rachit (Indian Journal of Dairy Science, 2014)
The present study made efforts to estimate costs and returns from milk production for different species of milch animals maintained by various land holding categories in plain & hill regions of the Nainital District of Uttarakhand state. In Plain region, cost of milk production per litre of milk, for local cow, crossbred cow and buffaloe was computed at Rs 27.61, Rs19.17 and Rs 27.19 respectively. Share of Feed cost in the total cost varied from 61 % (LC) to 64 % (CB& Buff).The share of labour cost ranged between 21 % (Buff) to 23 % (CB). The net returns were negative for the local cows, while, crossbred cows and buffaloes yielded positive net returns. In the case of hill region, cost of milk production per litre of milk, for local cow, crossbred cow and buffaloe was computed at Rs 26.47, Rs19.23 and Rs 26.88 respectively. Share of Feed cost in the total cost varied from 58 % (Buff.) to 64 % (CB). The share of labour cost ranged between 24 % (CB) to 30 % (LC & Buff). From the study, it can be summarized that by and large, irrespective of regions, local cow milk production suffered negative returns due to low productivity and over use of labour.